Motor competence of children with different levels of physical activity - Gojko Škundrić; Draženka Mačak; Snežana Damjanović; Boris Popović (University of Novi Sad, Faculty of Sport and Physical Education, 2023)
Adequate development, testing, continuous motor competence monitoring and physical fitness are very important factors in the development of children aged 7 to 10. The purpose of this study was to determine the differences in the motor competence of the children engaged in organized physical activities in sports clubs and the children who were not included in any kind of organized physical activity. The study included 119 children, 57 children engaged in organized activities in sports clubs (age: 8.44 ± 0.78; height: 133.17 ± 7.21; weight: 31.96 ± 7.73 BMI: 17.9 ± 3.38) and 62 children who had no additional organized physical activity (age: 8.43 ± 0.84; height: 134.85 ± 7.60; Weight: 34.44 ± 9.20 BMI: 18.7 ± 3.68). Motor competence was assessed by the Kiphard-Schilling body coordination test (KTK). After adjusting for age, gender, and BMI effects, we found small to medium significant mean differences (p<0.05, d [95%CI]) between the groups in hopping for height tests (d=0.78 [0.41, 1.16]), jumping sideways (d=0.79 [0.42, 1.17]), moving sideways (d=0.68 [0.32, 1.06]), and walking backward (d=0.44 [0.07, 0.81]). The results have shown that the children who were engaged in organized physical activities in sports clubs have a higher level of motor competence than their peers who were not included in the organized system in sports clubs. The authors strongly suggest that teachers, educators, coaches, and parents should encourage and include children in organized systems of physical activity, i.e., training processes in sports clubs.